STUDIA PODYPLOMOWE NA UCZELNIACH TECHNICZNYCH – DOSTOSOWANIE OFERTY EDUKACYJNEJ DO POTRZEB RYNKU PRACY - Sobotka, Bartosz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article examines the description and analysis of postgraduate programmes in Poland delivered as part of the continuing education process. Furthermore, the author of this article presents findings of his research on technical higher education institutions offering postgraduate programmes. Factors determining whether courses of study offered in a certain higher education institution (or academic units authorised to delivering such courses) meet current needs demonstrated on the labour market, stimulate development and effective functioning of the economy (factual benefits for development of companies) and satisfy expectations held by employers and employees willing to increase their professional skills. In the summary it is concluded that postgraduate programmes will be playing the key role on education market within life-long learning.